Mapeamento de aagravos em fauna silvestre urbana no município de São Paulo e cidades vizinhas através de animais recebidos no Centro de Recuperação de Animais Silvestres do Parque Ecológico do Tietê – CRAS-PET - Petri, Bruno Simões Sergio (2023)
With urbanization rates increasing globally, there is an immediate need to understand the type and nature of human-wildlife interactions. The state of São Paulo, located in the southeastern region of Brazil, together with the municipality of São Paulo (state capital) have one of the highest urbanization rates in the country, making this type of encounter (human being X wildlife) inevitable at some point. The wildlife rehabilitation center of Tietê park (CRAS – PET) is located in the east zone of the city of São Paulo and is one of the largest wildlife rehabilitations centers in the country in terms of number of animals received, the data collected there could elucidate in an unprecedented way what happens in the municipality and neighboring cities. Through the institution's electronic database, the causes of admission of 9828 animals were individually evaluated, which occurred between the years 2015 and 2021, from the capital and 12 other municipalities in greater São Paulo, of which 6303 animals belonged to the class AVE, 3148 belonging to the MAMMAL class and 377 to the REPTLIA class, with the city of São Paulo having the highest number of occurrences, with 58.6% of all animals received. After individual assessment of the animals' data, the injuries were classified into 5 major groups: Infectious Diseases, Occasional Capture, Orphanage, Splay leg and Trauma. In the AVE class, trauma was the main injury found, with collision being the most common type of trauma; Orphanage was the most important for MAMMAL and Occasional Capture for REPTILIA. For geocoding the addresses referring to the place where the injury occurred, the Geopy open source in Python was used and for mapping, free Qgis software was used with shapefiles of public domain. From the construction of the maps and application of the Kernel density estimation, it was possible to identify the main places in São Paulo and neighboring cities that most impact the urban wildlife, showing that, in the municipality of São Paulo, neighborhoods close to protected areas environment (urban parks) present higher and more constant numbers of injured animals.